Perceived attitudes and benefits towards teaching evidence based practice among physiotherapy lecturers at tertiary institutions in South Africa - J.M. Frantz; I. Diener (AOSIS, 2009)
Evidence-based practice (EBP) is gaining momentum in the physiotherapy profession. The main focus of EBP, however, has been in clinical practiceand in the move towards global EBP, very little attention has been given tothe contents of physiotherapy education programs. There is very limitedinformation regarding the attitudes of health professional lecturers, especially physiotherapists, towards the teaching of evidence based practice.The aim of this study was to determine the attitudes of lecturers and use ofevidence in teaching among physiotherapists at tertiary institutions in South Africa. The study employed a within stage mixed model approach. The study population consisted of all physiotherapy lecturers at the 8 training institutions in South Africa. Out of 76 physiotherapy lecturers at the 8 insti-tutions, the response rate to the questionnaire was 47% (35). Respondents identified that teaching EBP depends on personal experience, current literature, and availability of time, current practice patterns and CPD courses. Barriers toincluding evidence in the content of what is being taught were mainly time constraints, accessibility of journals, work-load and knowledge on how to obtain the evidence. Facilitators to including evidence in subject content were adequateresources and a well equipped library, the environment and departmental support/encouragement. Teaching EBPrequires the integration of factors such as research evidence, clinical expertise and patient values. Although the majority of respondents in the current study demonstrated a positive attitude towards teaching EBP, they reported finding it difficult to implement it in practice due to several identified barriers. It can only be to the benefit of lecturers, studentsand patients if university departments create favourable circumstances for lecturers to facilitate teaching of EBP.